Amyloid Beta and MicroRNAs in Alzheimer’s Disease - Amakiri, Nnana; Kubosumi, Aaron; Tran, James; Reddy, P. Hemachandra (Frontiers in Neuroscience, 2019)
Alzheimer’s disease (AD) is a progressive mental illness characterized by memory loss and multiple cognitive impairments. In the last several decades, significant progress has been made in understanding basic biology, molecular mechanisms, and development of biomarkers and therapeutic drugs. Multiple cellular changes are implicated in the disease process including amyloid beta and phosphorylation of tau synaptic damage and mitochondrial dysfunction in AD. Among these, amyloid beta is considered a major player in the disease process. Recent advancements in molecular biology revealed that microRNAs (miRNAs) are considered potential biomarkers in AD with a focus on amyloid beta. In this article we discussed several aspects of AD including its prevalence, classifications, risk factors, and amyloid species & their accumulation in subcellular compartments. This article also discusses the discovery and biogenesis of miRNAs and their relevance to AD. Today’s research continues to add to the wealth of miRNA data that has been accumulated, however, there still lacks clear-cut understanding of the physiological relevance of miRNAs to AD. MiRNAs appear to regulate translation of gene products in AD and other human diseases. However, the mechanism of how many of these miRNAs regulate both the 5’ and 3’UTR of amyloid precursor protein (APP) processing is still being extrapolated. Hence, we still need more research on miRNAs and APP/amyloid beta formation in the progression and pathogenesis of AD.